Dampak Penerapan Pola Tanam Padi Jajar Legowo terhadap Peningkatan Produksi Padi pada Petani Lokal di Desa Mungkung, Kalikajar, Wonosobo, Jawa Tengah - Wibowo, Bagus Setyo (Jurnal Ilmu-Ilmu Pertanian, 2025)
Increasing rice production is one of the strategic priorities in supporting national food security. The jajar legowo planting pattern is an innovative rice cultivation system designed to enhance land productivity through optimized spacing and better sunlight absorption. This study aims to analyze the impact of implementing the jajar legowo planting pattern on increasing rice production among local farmers in Mungkung Village, Kalikajar, Wonosobo, Central Java. A qualitative approach was applied, with data collected through in-depth interviews, direct field observations, and documentation. The respondents consisted of farmers who had implemented the jajar legowo system and local agricultural extension officers. The findings reveal that the adoption of the jajar legowo pattern increased yields by 15–25% compared to conventional planting methods, while also improving grain quality. Supporting factors include the availability of superior seeds, technical guidance from extension workers, and farmers’ awareness of the benefits of this planting system. Constraints identified were limited labor availability during planting, initial adaptation to the new technique, and additional costs for land preparation. These results confirm that the jajar legowo planting pattern can serve as an effective strategy for increasing rice production, particularly in highland areas such as Wonosobo.